2023
DOI: 10.1002/adfm.202308508
|View full text |Cite
|
Sign up to set email alerts
|

Customizing Hydrophilic Terminations for V2CTx MXene Toward Superior Hybrid‐Ion Storage in Aqueous Zinc Batteries

Chen Chen,
Tianhao Wang,
Xudong Zhao
et al.

Abstract: V2CTx MXene is a “rising star” cathode material for aqueous zinc‐based batteries (AZBs) owing to its large/flexible interlayer spacing, rich redox chemistry of V, and high electronic conductivity. Nevertheless, the plentiful F surface terminations generated during the common preparation (fluorine‐containing acid etching process) of V2CTx generally result in high hydrophobicity, poor Zn affinity, and sluggish ion‐diffusion kinetics. Herein, a novel OH‐termination‐rich V2CTx material with interlayer “K+‐pillars”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Figure (b) shows the XPS spectrum of V 2p with characteristics peaks linked to V 3+ , V 4+ , and V 5+ . The V 4+ species in V 2 C is associated with 516.9 and 425.5 eV, which confirm the existence of V 2 O 5 (V–O) on the surface of V 2 C. The binding energies at 516.1 and 517.9 eV are associated with V 3+ and V 5+ , respectively, confirming the presence of monolayer oxide/V 2 O 5 in the composite. , Comparing the results of V 2 C MXene and the V 2 C@V 2 O 5 /TiO 2 composite, it can be observed that various V 2 O 5 species are present in the composite, which was due to heating the samples at higher temperatures. Figure (c) shows the XPS spectrum of Ti 2p with binding energies of 458.8 and 463.7 eV, associated with Ti 2p 3/2 and Ti 2p 1/2 , respectively, which confirms the existence of Ti 4+ in V 2 C@V 2 O 5 /TiO 2 .…”
Section: Resultsmentioning
confidence: 53%
“…Figure (b) shows the XPS spectrum of V 2p with characteristics peaks linked to V 3+ , V 4+ , and V 5+ . The V 4+ species in V 2 C is associated with 516.9 and 425.5 eV, which confirm the existence of V 2 O 5 (V–O) on the surface of V 2 C. The binding energies at 516.1 and 517.9 eV are associated with V 3+ and V 5+ , respectively, confirming the presence of monolayer oxide/V 2 O 5 in the composite. , Comparing the results of V 2 C MXene and the V 2 C@V 2 O 5 /TiO 2 composite, it can be observed that various V 2 O 5 species are present in the composite, which was due to heating the samples at higher temperatures. Figure (c) shows the XPS spectrum of Ti 2p with binding energies of 458.8 and 463.7 eV, associated with Ti 2p 3/2 and Ti 2p 1/2 , respectively, which confirms the existence of Ti 4+ in V 2 C@V 2 O 5 /TiO 2 .…”
Section: Resultsmentioning
confidence: 53%
“…13 SA-3 exhibited the highest specific capacitance among the four samples because of the largest specific surface area and the appropriate amount of oxygen-containing functional groups. In order to explore the role of oxygen-containing functional groups 54,55 in the charge and discharge process (Fig. 5a), ex situ XRD, SEM, and XPS were measured.…”
Section: Resultsmentioning
confidence: 99%
“…Vanadium oxides have attracted extensive attention due to their open-frame crystal structure, which facilitates the mobility of Zn 2+ . However, certain challenges cannot be disregarded, such as an unstable layered structure and limited electronic conductivity, resulting in inadequate cycle capacity and stability. To overcome these obstacles, extensive efforts have been undertaken, such as the implementation of preintercalation techniques or defect engineering. One common approach involves the introduction of metal ions into the interlayer spacing of vanadium-based materials. This method aims to increase the interlayer spacing, create more diffusion channels, and enhance ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%